Races and populations of maize in Yugoslavia - Geric, I.; Zlokolica, M.; Geric, C.; Stuber, C.W. (1989)
This is the most extensive and the most complete study of genetic characteristics of populations in the Yugoslav corn collection conducted so far, using isozymes as gene markers.